Sustainable Volunteerism at a Major International Sporting Event: The Impact of Perceived Event Prestige - Seungmo Kim; Sung Il Hong; Damon P.S. Andrew (Journal of Applied Sports Management, 2013)
The primary purpose of the current study was to examine the impact of perceived event prestige (PEP) on intention to continue voluntary work via volunteer commitment and satisfaction at a globally prestigious sporting event. A total of 202 volunteers at the International Association of Athletics Federations (IAAF) Championship, held in August, 2011, in Daegu, South Korea, participated in the study. The results of structural equation modeling (SEM) supported the full mediating effects of both attitudinal variables between PEP and intention to continue voluntary work. In other words, volunteers are more likely to feel satisfied with their voluntary work and develop strong commitment toward the event when they perceive high levels of event prestige. In turn, high levels of volunteer satisfaction and commitment tend to increase volunteers’ intention to continue voluntary work for a future event. The results also revealed moderating effects of sport identification between PEP and both attitudinal outcomes.
Keywords: perceived event prestige; volunteer satisfaction; volunteer commitment; intention to continue volunteering; sport identification